(*)Bone Morphogenetic Protein 2 Alters Osteogenesis and Anti-Inflammatory Profiles of Mesenchymal Stem Cells Induced by Microtextured Titanium In Vitro - Hyzy, Sharon L. (Tissue Eng Part A, 2017)
Objectives: Microtextured titanium (Ti) induces osteoblast differentiation of mesenchymal stem cells (MSCs) in the absence of exogenous osteogenic factors; and high-energy surface modifications speed healing of microrough Ti implants. Bone morphogenetic protein 2 (BMP2) is used clinically to improve peri-implant bone formation and osseointegration but can cause inflammation and bone-related complications. In this study, we determined whether BMP2 alters human MSC differentiation, apoptosis, and inflammatory factor production when grown on Ti implants with different surface properties. Materials and Methods: Human MSCs were cultured on Ti substrates (smooth [PT], sandblasted acid-etched [SLA], hydrophilic-SLA [modSLA]), or tissue culture polystyrene (TCPS). After 7 days, inflammatory mRNAs were measured by polymerase chain reaction array. In addition, 7-day cultures were treated with exogenous BMP2 and osteogenic differentiation and production of local factors, proinflammatory interleukins, and anti-inflammatory interleukins assessed. Finally, osteogenic markers and interleukins were measured in MSCs cultured for 48 h on BMP2 dip-coated SLA and modSLA surfaces. Results: Expression of interleukins, chemokines, cytokines, and growth factors was affected by surface properties, particularly on modSLA. MSCs on Ti produced fewer resorptive and more osteogenic/anti-inflammatory factors than cells on TCPS. Addition of 100 ng/mL BMP2 not only increased differentiation but also increased proinflammatory and decreased anti-inflammatory/antiresorptive factors. Two hundred nanograms per milliliter BMP2 abolished osteogenesis and dramatically increased pro-osteoclastogenic factors. MSCs cultured on BMP2-dip-coated disks produced similar proinflammatory profiles with inhibited osteogenic differentiation and had increased apoptotic markers at the highest doses. Conclusions: MSCs underwent osteogenesis and regulated inflammatory cytokines on microtextured Ti. Exogenous BMP2 inhibited MSC differentiation and stimulated a dose-dependent proinflammatory and apoptotic response. Use of BMP2 with microtextured metal implants may increase inflammation and possibly delay bone formation dependent on dose, suggesting that application of BMP2 clinically during implant insertion may need to be reevaluated.